Peran Bagian SDM & Perlunya Perencanaan Karier bagi Karyawan - Rosalia Kurni Setyawati (Universitas Tarakanita, 2021)
Career planning is an important aspect in determining the direction of work and efforts to achieve self-development of an employee. Job profile identification, the ability to recognizing one's potential, setting targets and the ability to expand networks have an influence on one's struggle to achieve the desired targeted position. Career management is a process of determining steps or a work roadmap that relates several aspects. A person's career does not only depend on his own struggle but is also influenced by company policies and conditions. It is extremely necessary to consider that career management, brings positive effects, both for the employees and the company. A person's career development process needs to be realized from the start by setting targets, so that every movement of his work steps can be directed at achieving goals. The absence of a career management role can result in a lack of employee growth and self-development, a less than optimal exploration of employee capabilities, and a lack of increasing company productivity.